Vijayanagaracā Samrāṭa Kr̥shṇadevarāya - Āṭhavale, Sadāśiva, 1922- (Puṇe : Śrīvidyā Prakāśana, 1999)
Biography of Krishnadeva Raya, King of Vijayanagar, d. 1529 or 30.
Includes bibliographical references (p. [186]-187) and index.
Mode of access: Internet.
In Marathi.
Keywords: Krishnadeva Raya, -- King of Vijayanagar, -- -1529 or 1530.; Vijayanagar (Empire) -- History -- 16th century; Vijayanagar (Empire) -- Kings and rulers -- Biography